Fatal spontaneous rupture of splenic artery aneurysm in third trimester pregnancy - Samberkar, Prashant Naresh; Chow, Tak Kuan; Samberkar, Snehlata Prashant (College of Pathologists, Academy of Medicine Malaysia, 2018)
Introduction: Unforeseen emergency in late pregnancy can be catastrophic and cause unexpected maternal and foetal demise. Moreover, lack of awareness and failure of prompt treatment raise mortality rate. Such fatalities warrant a forensic autopsy as it may raise redundant medico-legal concerns. Case Report: We report a case that revealed significant intra-abdominal haemorrhage at autopsy. The source of haemorrhage was at the spleen hilum and histology established rupture of splenic artery aneurysm. There was no associated obstetric cause found. Conclusion: Knowledge of spontaneous rupture of splenic artery aneurysm in late pregnancy is essential for monitoring maternal and foetal, morbidity and mortality. However, in the eventuality of death a comprehensive forensic autopsy is the only investigation to recognise such calamity and clear clinical confusion.